In vitro seed germination of Coelogyne asperata Lindl. (Orchidaceae) - Arnnyitte Alexander; Jualang Azlan Gansau; Devina David (UniSE Press, 2021)
A protocol for in vitro seed germination of Coelogyne asperata Lindl. has been established successfully. Immature seeds from 182 days old capsule were cultured on three different basal media; Murashige and Skoog (MS), Knudson C (KC), and Vacin and Went (VW) and maintained under continuous light at 25 ± 2 ˚C. After 30 days of culture (DAC), more than 90% of seeds were germinated on KC and VW media and about 84% of seeds germinated on MS medium. The incorporation of organic additives, including coconut water, potato homogenate and tomato juice each at 10% (v/v) in KC medium was tested to determine their effect on seed germination of C. asperata. The result revealed that KC basal medium alone without addition of organic additives promoted over 90% of seed germination at 30 DAC. Therefore, the protocol of using standard KC basal medium for C. asperata seeds germination could be suggested for mass propagation and conservation of this wild scented orchid.